2016
DOI: 10.1002/bjs.10112
|View full text |Cite
|
Sign up to set email alerts
|

Validation of preoperative cardiopulmonary exercise testing-derived variables to predict in-hospital morbidity after major colorectal surgery

Abstract: These data provide further evidence that variables derived from preoperative CPET can be used to assess risk before elective colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 30 publications
2
107
1
Order By: Relevance
“…These issues affect statistical analysis and generalisability, as does the fact that the thresholds for risk of the peak oxygen uptake and ventilatory anaerobic threshold were based on the cut-off points described in another study and patient population [12]. Firstly, due to the retrospective evaluation of the tests, there is a possibility of bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These issues affect statistical analysis and generalisability, as does the fact that the thresholds for risk of the peak oxygen uptake and ventilatory anaerobic threshold were based on the cut-off points described in another study and patient population [12]. Firstly, due to the retrospective evaluation of the tests, there is a possibility of bias.…”
Section: Discussionmentioning
confidence: 99%
“…These peak oxygen uptake and ventilatory anaerobic threshold values are based on the cut-off points described by West et al [12]. Tests for normality were performed with the Shapiro-Wilk test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of CPET to identify patients at risk of poor outcomes is used clinically to guide perioperative care and clinical decision making, and it informs about the shared decision‐making process . We have previously reported that selected CPET variables such as oxygen uptake at estimated lactate threshold or anaerobic threshold ( trueV̇O 2 at AT) and at peak exercise ( trueV̇O 2 peak) are associated with worse outcome following colorectal surgery and neoadjuvant cancer treatments . Poor physical fitness is highly prevalent in HPB cancer patients and associated with poor post‐operative outcomes and survival …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review [47**] from 37 studies including 7852 patients concluded CPET was a useful preoperative risk-stratification tool able to predict postoperative outcome in patients across a range of surgical specialties, but further research was needed to justify ability of CPET to predict postoperative outcome. Following this review, the first multi-center perioperative CPET study[48**] evaluated the relationship between CPET measurements and in-hospital morbidity in 703 patients undergoing major elective colorectal surgery in 6 centers. Consistent with previous studies, both anaerobic threshold and peak oxygen consumption (VO 2 P) were predictive of postoperative morbidity with area under the ROC curve (AUROC) of 0·79 and 0·77 respectively.…”
Section: Personalizing Prehabilitative and Post-icu Exercise Intervenmentioning
confidence: 99%